“Agrifun” untuk Keberlangsungan Usaha BUMDes Karangrejo, Kecamatan Borobudur - HO Siregar; AR. Jatmiko (SULUH: Jurnal Abdimas, 2020)
Village-owned enterprises is a business unit established and managed by villagers. Having different characteristics between one village and another village in accordance with the advantages and potential of each. Karangrejo Village is located in the Borobudur Temple area as a unique opportunity for tourism development. This village chose to develop agro-tourism under the name Kampung Palawija and Kampung Organic. However, currently Village-Owned Enterprises has no manager and management because of the decline in agricultural attractiveness for villagers. To overcome this problem the service team provided solutions to the problem, namely by the method of "agrifun" and training on Village-Owned Enterprises agro-tourism management. The results obtained from this activity are rising agricultural interest for children who in the future will manage and adding agro-tourism activities and good managing Village-Owned Enterprises. With this resulting can guarantee Village-Owned Enterprises has sustainable in long time.